Fast Adapting Ensemble: A New Algorithm for Mining Data Streams with Concept Drift - Agustín Ortíz Díaz; José del Campo-Ávila; Gonzalo Ramos-Jiménez; Isvani Frías Blanco; Yailé Caballero Mota; Antonio Mustelier Hechavarría; Rafael Morales-Bueno (The Scientific World Journal)
The treatment of large data streams in the presence of concept drifts is one of the main challenges in the field of data mining, particularly when the algorithms have to deal with concepts that disappear and then reappear. This paper presents a new algorithm, called Fast Adapting Ensemble (FAE), which adapts very quickly to both abrupt and gradual concept drifts, and has been specifically designed to deal with recurring concepts. FAE processes the learning examples in blocks of the same size, but it does not have to wait for the batch to be complete in order to adapt its base classification mechanism. FAE incorporates a drift detector to improve the handling of abrupt concept drifts and stores a set of inactive classifiers that represent old concepts, which are activated very quickly when these concepts reappear. We compare our new algorithm with various well-known learning algorithms, taking into account, common benchmark datasets. The experiments show promising results from the proposed algorithm (regarding accuracy and runtime), handling different types of concept drifts.